THE STATE OF ORAL CAVITY IN THE DRUG-DEPEDENT PATIENTS - Petrushanko, T.O.; Boichenko, O.M.; Popovych, I.Yu.; Gryshchenko, V.V. (World of Medicine and Biology, 2021)
The study presents the assessment of the state of oral cavity in patients addicted to drugs depending on the duration of drug use. A total of 45 drug-dependent men and women aged 20 to 50 have been examined. The findings of the study indicate a significantly higher percentage of diseases of the hard dental tissues, periodontium and oral mucosa compared to people who have not used drugs. The conclusions of the study necessitate a significant amount of dental care for drug-dependent patients, both for dental diseases and periodontal tissues, oral mucosa. Generalized periodontitis of the III degree of severity was observed in 75 % of the first group. All 50 % of patients in the second group had an exacerbated course of generalized periodontitis. At the same time, the average value of the hygienic index in the first group was 2.20±0.15 (р